Od abstraktnosti mita o Faroniki do alegorične konkretizacije teorije o Gaji From the Abstract Myth about Faronika to the Allegoric Concretisation of the Theory of Gaia - Irena Pangeršič (Studia Mythologica Slavica, 2012)
In the article is discussed the connection between the myth about the fish Faronika and the metheorological and seismological phenomenons on the planet Earth.